Implementation of coaching methods in Islamic Religious Education learning at Elementary school 1 and 2 Maitara Island, Tidore Islands (Eurasian Journal of Learning and Academic Teaching, 2026)
This study aims to describe the implementation of the coaching method in learning Islamic Religious Education (PAI) on the motivation and understanding of students in Elementary school 1 and Elementary school 2 Maitara Island, Tidore Islands City. The research method used is a qualitative approach with a descriptive type. Data collection techniques are carried out through interviews, observations, and documentation. The research informants consisted of Islamic Religious Education teachers and students of grades IV and V. Data analysis was carried out through data reduction, data presentation, and conclusion drawn.